An introduction to mutual funds worldwide - Russell, Ray 1944- (Wiley, 2007)
This guide explains what mutual funds are, how they have developed and how they are used, regulated and administered across the globe. Both open-ended and closed-ended funds are described and the differences between the international markets, particularly USA, Europe and UK are addressed.